Antimicrobial efficacy and toxicity profiles of conventional antimicrobial agents in combination with commercially relevant southern African medicinal plants - Hubsch, Zelna (My University, 2014)
Traditional medicine plays a vital role in the cultural heritage of many South Africans, with at least 80% of the population relying on medicinal plants for their primary source of healthcare. It has been acknowledged that even in some of the finest hospitals in South Africa, people are often found to be using traditional medicine in combination with conventional treatment regimens. Despite the substantial use of medicinal plants in South Africa, limited information is available on the interactive properties between commercially relevant, southern African medicinal plants and conventional drugs. Furthermore, the potential for toxicity of these combinations has been sorely neglected. In orthodox medicine, antimicrobials such as antibiotics and antifungals are amongst the most commonly prescribed group of drugs. Therefore, there is a high probability for the concurrent use of these two forms of healthcare. The aim of this study was to evaluate the interactive antimicrobial and toxicity profiles, when seven conventional antimicrobial agents (amphotericin B, ciprofloxacin, erythromycin, gentamicin, nystatin, penicillin G and tetracycline) were combined with the essential oils, aqueous and organic extracts of seven medicinal plants (Agathosma betulina, Aloe ferox, Artemisia afra, Aspalathus linearis, Lippia javanica, Pelargonium sidoides and Sutherlandia frutescens). The antimicrobial activity of the plant samples and conventional antimicrobials were evaluated, alone and in combination, using the minimum inhibitory concentration (MIC) assay against two yeasts, three Gram-positive and three Gram-negative bacteria. The combinations were further evaluated using the fractional inhibitory concentration (ΣFIC) assessment. Combinations demonstrating notable synergistic or antagonistic interactions were studied in various ratios (isobolograms). Toxicity of the antimicrobials and plant samples were assessed, individually and in combination, using the brine-shrimp lethality assay (BSLA) and the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) cell proliferation assay on human kidney epithelial cells (Graham or HEK-293 cell line). A total of 476 combinations were assessed for interactive antimicrobial potential. Of these combinations, 14.29% were synergistic, 7.56% antagonistic, 35.71% additive and 42.44% indifferent in nature. Some notable interactions were identified, such as the combination of A. linearis (aqueous and organic extract) with penicillin G, where a synergistic profile was most often seen against the three tested Gram-positive micro-organisms (Staphylococcus aureus, Bacillus cereus and Enterococcus faecalis), with ΣFIC values ranging from 0.01 (synergistic) to 0.94 (additive). Further notable interactions included A. betulina and S. frutescens, when combined with ciprofloxacin and tested against E. coli, which demonstrated a favourable synergistic profile, and could be of importance in the treatment of urinary tract infections. In the BSLA, the notable interactions that were tested demonstrated no toxic effect. In the MTT cellular viability assay, the only combination demonstrating possible toxicity was that of A. linearis (aqueous and organic extract) in combination with nystatin (inhibitory effects of 73.76 ± 3.36% and 56.88 ± 6.61%, respectively). Therefore, concurrent use should be cautioned and further in vivo studies warranted. In conclusion, most combinations were found to be non-interactive, alleviating some of the concern related to the concurrent use of the two forms of healthcare. However, some notable combinations were identified, which could possibly have an impact on conventional treatment regimens. Therefore, further in vivo testing is warranted to support the in vitro findings.
Thesis (M.Pharm.)--University of the Witwatersrand, Faculty of Health Sciences, 2014.
Keywords: Plants, Medicinal; Medicine, Herbal